2016
DOI: 10.1021/acs.jcim.6b00079
|View full text |Cite
|
Sign up to set email alerts
|

Alchemical Free Energy Calculations and Isothermal Titration Calorimetry Measurements of Aminoadamantanes Bound to the Closed State of Influenza A/M2TM

Abstract: Adamantane derivatives, such as amantadine and rimantadine, have been reported to block the transmembrane domain (TM) of the M2 protein of influenza A virus (A/M2) but their clinical use has been discontinued due to evolved resistance in humans. Although experiments and simulations have provided adequate information about the binding interaction of amantadine or rimantadine to the M2 protein, methods for predicting binding affinities of whole series of M2 inhibitors have so far been scarcely applied. Such meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 122 publications
8
56
0
Order By: Relevance
“…The angle between the pore axis or the normal of the membrane and C−N bond vector was ∼11°for 1 and close to 50°for 2-R, 2-S, and 3. These angle values suggest that the ammonium group of all aminoadamantane compounds is oriented toward the C-terminus, in consistency with previous experimental findings 6,7,9 and MD simulations 13,32,36 (Table S1). The distance between the adamantyl ring and the center of mass between the four A30 (Ad-A30) for 1−3 was measured ∼1 Å, and the distance CH 3 (lig.…”
Section: Acs Medicinal Chemistry Letterssupporting
confidence: 91%
See 1 more Smart Citation
“…The angle between the pore axis or the normal of the membrane and C−N bond vector was ∼11°for 1 and close to 50°for 2-R, 2-S, and 3. These angle values suggest that the ammonium group of all aminoadamantane compounds is oriented toward the C-terminus, in consistency with previous experimental findings 6,7,9 and MD simulations 13,32,36 (Table S1). The distance between the adamantyl ring and the center of mass between the four A30 (Ad-A30) for 1−3 was measured ∼1 Å, and the distance CH 3 (lig.…”
Section: Acs Medicinal Chemistry Letterssupporting
confidence: 91%
“…The ssNMR results for 2 also demonstrated that the ammonium group of the drug is pointing toward the four H37 residues at the C-terminus. 9 This orientation can be stabilized either through hydrogen bonds between the ammonium group of the aminoadamantane ligand and water molecules in the channel lumen which exist between the imidazoles of H37 and the ligand, 13 and/or with A30 carbonyls in the vicinity, 14 according to experimental 9,14−16 and MD simulations data. 13,17−22 Provided that M2TM is a minimal model for M2 binding, 10 these high resolution structures can be used for the development of new ligands which may bind more effectively to the M2TM pore.…”
mentioning
confidence: 99%
“…Since 2005, the amantadine (1)-insensitive Ser-to-Asn mutation at position 31 in M2 (S31N) has become globally prevalent, abrogating the clinical usefulness of 1. 10 Compound 2 is ranked among the best binders to M2TM WT 11,12 and most potent anti-IAV agents among the aminoadamantane derivatives. 13,14 Thus, the synthesis of symmetrical analogues of 2 with the addition of two methyl (3), ethyl (4), and n-propyl (5) groups on the carbon bridge was accomplished (Scheme 1) aiming at filling progressively from 3 to 5 the extra space between the ligand and the walls in M2 WT or M2 S31N with a few alkyl groups.…”
mentioning
confidence: 99%
“…In addition, positively charged fragment-like molecules, such as amantadine (44) and 2-guanidinobenzimidazole (2GBI) (30), are known to act as pore blockers of M2 and Hv1, respectively. Many groups, including ours, have successfully pursued drug discovery projects with M2 as a target (45)(46)(47)(48)(49)(50)(51)(52)(53). In particular, we have recently shown that scaffold replacement of hydrogen-bonded Significance Hv1, a voltage-gated proton channel, is an emerging pharmacological target implicated in many pathological conditions, including cancer and ischemic brain damage.…”
mentioning
confidence: 99%